Pertanggungjawaban Pidana Rumah Sakit Terhadap Malpraktek Medik Di Rumah Sakit - Robert Valentino Tarigan; mahmud mulyadi; M Ekaputra; Mahmul Siregar (Iuris Studia: Jurnal Kajian Hukum, 2021)
Hospital in implementing health services is not always the medical service provided by health workers in the hospital, it can provide the results expected by all parties. Not a few hospitals due to the negligence of their doctors in providing health services made the mistake of committing medical malpractice. Article 46 of Law Number 44 Year 2009 states that "the hospital is legally responsible for all losses caused by negligence committed by health workers in the hospital". Articles 190 and 201 of Law Number 36 of 2009 concerning Health regulate the provision of criminal responsibility not only to doctors but also to hospitals, which legally are doctors and the facilities and services are provided by the hospital. The problems that will be discussed in this research are: 1. How is the doctrine of corporate criminal responsibility regulated in the laws and regulations in Indonesia? 2. What is the role and position of the hospital which is categorized as a corporation? 3. How is the criminal responsibility of the hospital for medical malpractice in the hospital? Based on the results of research and discussion that the doctrine of corporate criminal responsibility which is regulated in the laws and regulations in Indonesia, especially in the Law on stockpiling of goods adheres to the doctrine of Direct Liability and Vicarious Liability, UU Number 44 of 2009 concerning Hospitals adheres to the doctrine of the corporate culture model of doctrine, while Law Number 36 of 2009 adheres to the doctrine of delegation. Perma Number 13 of 2016 adopts the corporate culture model theory. The role of hospitals that are categorized as corporations is based on the hospital definition that hospitals are health service institutions based on the provisions of Article 7 of Law Number 44 of 2009 concerning hospitals must be a legal entity. This legal entity is a corporation when viewed in a broad sense such as the existence of PT, CV, Foundation and other forms of legal entities. Hospital criminal liability for medical malpractice in the hospital If viewed from the point of view of the hospital, the hospital's responsibility itself includes three things, namely: responsibilities relating to personnel, responsibilities relating to facilities and equipment, responsibilities relating to the duty of care. provide good care). Corporations or hospital legal entities can also be prosecuted as the perpetrator of a criminal act based on the provisions of Article 80 paragraph (2) and Law Number 29 of 2004 concerning Medical Practice as well as Article 190 Jo. Article 201 of Law Number 36 Year 2009 concerning Health